THE IMPACT OF ORGANIC FERTILIZER ON THE GROWTH AND PRODUCTION OF ONION (ALLIUM ASCALONICUM L.) - Irfan Abdullah; Tharmizi Hakim; Zamriyetti (RADJA PUBLIKA, 2024)
Due to climate change, pest and disease attacks, unbalanced use of seeds and fertilizer use, shallot production in North Sumatra still does not meet consumer demand. This research used a Randomized Block Design with 2 factors and 2 replications. The first factor is POP (Solid Organic Fertilizer) consisting of 4 concentration levels, namely P0 = 0 kg/plot, P1 = 4.5 kg/plot, P2 = 7.5 kg/plot, and P3 = 10.5 kg/plot. The second factor is POC (Liquid Organic Fertilizer) consisting of 4 concentration levels, namely C0 = 0 ml/liter water/plot, C1 = 250 ml/liter water/plot, C2 = 450 ml/liter water/plot, and C3 = 650 ml /liter of water/plot. The results of the growth research showed that the highest POP was in P3 with a plant height of 35.76 cm, number of tillers 1.72 and tuber diameter 37.01 cm and the highest POC treatment was in C2 treatment with number of tillers 1.51 cm and tuber diameter 3.28 cm . Production showed that the highest POP was in P3 with a wet tuber weight of 45.28 gr, a dry tuber weight of 31.82 gr, and a production conversion per hectare of 55.80 kg, for the highest POC was in C2 with a wet tuber weight of 40.70 gr, tuber weight dry 31.82 gr and production conversion per hectare 51.39 kg. This research shows an increase in the growth and production of shallot plants.